The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1371/journal.pone.0216281
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of white and yellow eye colour mutant strains of house cricket, Acheta domesticus

Abstract: Two eye-colour mutant strains, white (W) and yellow (Y) of house cricket Acheta domesticus were established in our laboratory. We phenotyped and genotyped the mutants, performed genetic crossings and studied the eye structure and pigment composition using light and electron microscopy and biochemical analysis. We show that W and Y phenotypes are controlled by a single autosomal recessive allele, as both traits are metabolically independent. The analysis of the mutants`eye structure showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
2
4
0
Order By: Relevance
“…We were able to unequivocally demonstrate that w and cn are located on autosomes; furthermore, genotyping of both w and cn mutant individuals from G1, G2 and G3 indicated that both males and females carried two alleles for each of these genes. This contrasts to the X-linked inheritance of w in D. melanogaster 49 , but is consistent with the autosomal location of w in the hemimetabolous house cricket, Acheta domesticus 50 . Given the conservation of X-linked genes in three hemipteran insects ( O. fasciatus , the brown marmorated stink bug ( Halyomorpha halys) and GWSS) with different sex determination systems (XX/XY, likely male heterogametic , and XX/XO, respectively ), it will be interesting to determine if the autosomal location of w will be maintained across the Hemiptera 48 .…”
Section: Discussionsupporting
confidence: 79%
“…We were able to unequivocally demonstrate that w and cn are located on autosomes; furthermore, genotyping of both w and cn mutant individuals from G1, G2 and G3 indicated that both males and females carried two alleles for each of these genes. This contrasts to the X-linked inheritance of w in D. melanogaster 49 , but is consistent with the autosomal location of w in the hemimetabolous house cricket, Acheta domesticus 50 . Given the conservation of X-linked genes in three hemipteran insects ( O. fasciatus , the brown marmorated stink bug ( Halyomorpha halys) and GWSS) with different sex determination systems (XX/XY, likely male heterogametic , and XX/XO, respectively ), it will be interesting to determine if the autosomal location of w will be maintained across the Hemiptera 48 .…”
Section: Discussionsupporting
confidence: 79%
“…The spectra matched the ommatin group of ommochromes (Sawada et al, 2000). The wide bands (360-650 nm) are attributed to a combination of different ommochrome compounds (Liu et al, 2012;Francikowski et al, 2019). The main absorbance peaks detected in ommochromes can shift; however, the most common shifts reported for xanthommatin and dihydroxanthommatin are observed in the UV, near UV, and 430-520 nm ranges (Riou & Christidès, 2010;Figon & Casas, recorded at 734 nm using a UV spectrophotometer (Multiskan GO, Thermo Scientific).…”
Section: Antioxidant Activitymentioning
confidence: 70%
“…However, the most intriguing candidate gene ( predicted gene g6064) is located approximately 118 kilobase pairs away from outlier 2 and is homologous to the Punch (Pu) gene in D. melanogaster (table 1). This gene codes for a GTP cyclohydrase I enzyme, which is involved in the first step of the production of pteridine pigments in D. melanogaster and other insects, and is associated with eye and body coloration in multiple insect species [37][38][39][40]59]. This led us to hypothesize that this SNP could also be associated with T. chumash eye coloration, a trait that we observed to be quite variable but which is previously unstudied in this species (electronic supplementary material, figure S2).…”
Section: (C) Potential Function Of the Two Lt-mapit Outlier Single-nu...mentioning
confidence: 99%
“…Chitinases are associated with cold or heat stress tolerance in several insect species [35,36] suggesting that this locus could be associated with heat tolerance in Timema. However, the most intriguing candidate, Punch, controls the first step of pteridine pigments production and is associated with eye and body coloration in many insect species [37][38][39][40]. This led us to hypothesize that this locus could be primarily associated with eye colour variation in T. chumash.…”
Section: Introductionmentioning
confidence: 99%